2020
DOI: 10.1155/2020/6281454
|View full text |Cite
|
Sign up to set email alerts
|

Foods with Potential Prooxidant and Antioxidant Effects Involved in Parkinson’s Disease

Abstract: Oxidative stress plays a fundamental role in the pathogenesis of Parkinson’s disease (PD). Oxidative stress appears to be responsible for the gradual dysfunction that manifests via numerous cellular pathways throughout PD progression. This review will describe the prooxidant effect of excessive consumption of processed food. Processed meat can affect health due to its high sodium content, advanced lipid oxidation end-products, cholesterol, and free fatty acids. During cooking, lipids can react with proteins to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 227 publications
(256 reference statements)
1
16
0
Order By: Relevance
“…It is widely accepted that ROS plays a critical role in GV-mediated damage. 8 We demonstrated that the ROS scavenger NAC, which shows antioxidant properties by replenishing cellular GSH and participating in endogenous antioxidant systems, 42 reduced GV-treated neuronal cells apoptosis and ROS levels in GV-treated hippocampal neuronal cells and alleviated the mitochondrial Ca 2+ uptake. There is a feed-forward, self-amplified loop between the Ca 2+ -modulated generation of ROS and the ROS-induced increase of Ca 2+ .…”
Section: Discussionmentioning
confidence: 91%
“…It is widely accepted that ROS plays a critical role in GV-mediated damage. 8 We demonstrated that the ROS scavenger NAC, which shows antioxidant properties by replenishing cellular GSH and participating in endogenous antioxidant systems, 42 reduced GV-treated neuronal cells apoptosis and ROS levels in GV-treated hippocampal neuronal cells and alleviated the mitochondrial Ca 2+ uptake. There is a feed-forward, self-amplified loop between the Ca 2+ -modulated generation of ROS and the ROS-induced increase of Ca 2+ .…”
Section: Discussionmentioning
confidence: 91%
“…In different types of in vitro gastric model tests, 100-fold increase in the level of lipid hydroperoxides has been observed [ 34 ]. Proteins and lipids oxidized by these catalytic molecules, which can be found in significant quantities in processed meat, butter, and some heated plant-based oils (such as olive oil), may affect the development of Parkinson’s disease [ 35 ], inflammatory bowel disease [ 36 ], and insulin resistance [ 37 ].…”
Section: Antioxidantsmentioning
confidence: 99%
“…Transmission electron micrographs revealed that mitochondrial damage was more severe in AdipoR1 CKO mice than in AdipoR1 flox/flox mice after TBI. Since the mitochondria is the main source of cellular ATP and plays an essential role in cell survival, growth, metabolism, oxidative injury, and apoptosis, mitochondrial dysfunction is a common feature of many diseases [ [76] , [77] , [78] , [79] , [80] , [81] ]. Further, we investigated the potential mechanisms of APN/AdipoR1 signaling on the mitochondria.…”
Section: Discussionmentioning
confidence: 99%